PENGARUH KARAKTERISTIK TIM, PENGETAHUAN MANAJEMEN, DAN ETIKA KERJA TERHADAP KINERJA KETUA PROGRAM STUDI PADA SEKOLAH TINGGI ISLAM SWASTA DI PROVINSI JAMBI - Ahmad Ridwan (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2018)
ABSTRACTThe objective of the research is to obtain information concerning the effect ofteam characteristics, management knowledge, and job ethics, on heads ofstudy program performance. The research was carried out by means ofsurvey in Jambi Province, involving 75 heads of study program asrespondents who are selected through simple randomsampling and the datahas been analysed by path analysis after all variables put into thecorrelationmatrix. (1) there is a direct effect of team characteristics on heads ofstudyprogram performance.(2) there is direct effect management knowledgeon heads of studyprogram performance. (3) there is a direct effect job ethicson heads of study programperformance . (4) there is a direct effect of teamcharacteristics on job ethics, and (5) there is a direct effect managementknowledge on job ethics. Therefore, the variation ofheads of study programperformance are effected by the variation of team characteristics,variationmanagement knowledge, variation job ethics. Keywords: team characteristics, management knowledge, job ethics andheadsof study program performance.